Strategic management in Finnish and Norwegian government agencies - Jan-Erik Johanson; Åge Johnsen; Elias Pekkola; Stephen Affleck Reid (Administrative Sciences, 2019)
The purpose of this article is to analyse the design and implementation of strategic planning and performance management in governmental agencies in two Nordic countries, Finland and Norway. Nordic countries are an interesting study from a comparative perspective because while they are commonly assumed to have been high-intensity new public management reformers, they are also commonly assumed to have a distinct public management tradition. Moreover, these two countries are interesting to study because within the Nordic public management tradition, Finland and Norway specifically represent two different public management traditions. Finland belongs to the Eastern Nordic public management tradition, with an emphasis on decentralisation and agency autonomy, while Norway belongs to the Western Nordic public management tradition, with an emphasis on hierarchical governance, and hence, much performance management and reporting. Therefore, we expected to find more decentralised strategic management and an emphasis on evaluation in Finland, and more central, planning-like strategic management and reporting in Norway. Our comparison shows that both countries had mandatory strategic planning and utilised decentralised strategic planning in government agencies. The stronger legal orientation in the public administration in Finland, however, made strategic changes more complicated in Finland than in Norway.
Keywords: 350; agency governance; central government organisations; formal strategic planning; Nordic administrative traditions; performance management; strategy content